Active Moderate-to-Severe Graves' Orbitopathy in a Patient With Type 2 Diabetes Mellitus and Vascular Complications - Urselli, Francesca; Pontieri, Gilda; Peschi, Livia; Liccardi, Alessia; Ruggiero, Anna Rita; Biondi, Bernadette (Frontiers in Endocrinology, 2019)
Background: Graves' orbitopathy (GO) is the main extrathyroidal manifestation of Graves' disease (GD). Diabetes mellitus (DM) has been reported to be a risk factor in patients with GO. Moreover, GO can be more frequent and severe in type 2 diabetes patients. High doses of intravenous glucocorticoids represent the first line treatment of moderate-to-severe and active GO according to the international guidelines. However, this therapy is contraindicated in uncontrolled diabetes and in patients with increased cardiovascular risk. Some anti-diabetic drugs can exacerbate GO. We reported the clinical case of an active and moderate-to-severe GO in a patient with uncontrolled type 2 DM and vascular complications. Case Report: A 61-years-old patient came to our ambulatory for a recurrence of GD and a moderate-to-severe bilateral GO. The patient had uncontrolled type 2 DM during insulin therapy and a history of micro and macrovascular complications. At the physical examination, the clinical activity score was 5 and the severity of GO was moderate-to-severe. A blood sample showed overt hyperthyroidism and the persistence of anti-TSH receptor antibodies (TRAb) during treatment with methimazole. A computed tomography scan showed a moderate-to-severe bilateral exophthalmos. We discuss the benefit/risk of treatment of GO in our patient. Conclusion: The available guidelines do not focus on the treatment of diabetic patients with uncontrolled diabetes and severe vascular complications, therefore our patient represents a difficult therapeutic challenge. The screening of thyroid function and the evaluation of GO could be useful in diabetic patients with autoimmune thyroid disease to perform a correct treatment of these disorders.